Boundedness of Multilinear Oscillatory Singular Integral on Weighted Weak Hardy Spaces (Analysis in Theory and Applications, 2017)
In this paper, by using the atomic decomposition of the weighted weak Hardy space $WH_ω^1(\mathbb{R}^n)$, the authors discuss a class of multilinear oscillatory singular integrals and obtain their boundedness from the weighted weak Hardy space $WH_ω^1(\mathbb{R}^n)$ to the weighted weak Lebesgue space $WL_ω^1(\mathbb{R}^n)$ for $ω\in A_1(\mathbb{R}^n)$.